Low-temperature resistance of fluorine rubber with modified Si-based nanoparticles. (December 2022) - Ma, Yucong; Ding, Ang; Dong, Xufeng; Zheng, Shunqi; Wang, Tianjiao; Tian, Ruixue; Wu, Aimin; Huang, Hao
Abstract: Fluorine rubber contains fluorine atoms with strong electronegativity, which endow it with novel properties, such as oil resistance, heat resistance, chemical resistance, but also lead to poor low temperature resistance. Si-based nanoparticles are used as the new active crosslinking point of fluorine rubber, which can break the original regular structure to improve the low-temperature resistance and ensuring the mechanical properties of fluorine rubber. The relative optimal silane coupling agent is selected according to the relative concentration and the interaction energy of the molecular interface in different models. The optimal silane coupling agent can avoid the agglomeration of Si-based nanoparticles in fluorine rubber and form flexible bridge between inorganic Si-based nanoparticles and fluorine rubber long chains. It is discovered that the mechanical and low-temperature properties of the modified Si-based nanoparticles/fluorine rubber (FKM-M Si) was optimal compared with pure fluorine rubber (P-FKM) and unmodified Si-based nanoparticles/fluorine rubber (FKM-UM Si). The brittleness temperature (Tb ) is reduced from − 18.0 °C to − 29.0 °C, allowing for a wider range of applications for FKM-M Si. This study provided a potential for the application of fluorine rubber composites in harsh low-temperature environment. Graphical Abstract: ga1 Highlights: The silicon nanoparticles have larger Si–O–Si bond angles, high orientation freedom and good flexibility. Improving the dispersion of silicon nanoparticles in fluorine rubber by chemical modification. Unique nanocomposite structure is the key point of the low temperature resistance.